To evaluate the expression \((13 + \sqrt{-225}) - (49\sqrt{-2}i)\), we will first simplify each component.
-
Simplify \(\sqrt{-225}\): \[ \sqrt{-225} = \sqrt{225} \cdot \sqrt{-1} = 15i \]
-
Simplify \(49\sqrt{-2}\): \[ \sqrt{-2} = \sqrt{2} \cdot \sqrt{-1} = \sqrt{2}i \] Thus, \[ 49\sqrt{-2} = 49\sqrt{2}i \]
Now substitute these values into the original expression:
\[ (13 + 15i) - (49\sqrt{2}i) \]
Combine the imaginary parts:
\[ = 13 + (15i - 49\sqrt{2}i) \] \[ = 13 + (15 - 49\sqrt{2})i \]
Final result in the form \(a + bi\):
\[ = 13 + (15 - 49\sqrt{2})i \]
So, the answer is:
\[ \boxed{13 + (15 - 49\sqrt{2})i} \]